PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA AKUNTAN INTERN - ., SARSITI (Universitas Surakarta, 2011)
The study aimed to determine the effect of (1) Motivation on Performance Accounting Intern (2) Job Satisfaction to Performance Intern Accountant. This study used a survey method. The population was Accountant Intern in the manufacturing industry in the city of Surakarta by using convenience sampling. By using SPSS statistical analysis, the results of hypothesis testing (t test) for motivation obtained t 3.438 with a significant level of 0.003 > 0.05. This shows that H0 is rejected and H1 successfully supported statistically. Job satisfaction showed tcount ttable is smaller than -1.105 and significant value 0.132>0.05 then H3 is not supported statistically successful. F test results produce the F-count of 3.109 and F-table of 2.93. This means that the F-count > F -table so it can be concluded that there is a significant effect of simultaneous independent variables on the performance of the internal auditor. The coefficient of determination (Adjusted R Square) is sebesat 0.239. This indicates that only 23.9 % of internal accounting performance variables can be explained by the motivation and job satisfaction, while the remaining 76.1 % is explained by other variables that are not used in this study. Keywords;Â Â motivation , job satisfaction and performance Intern accountant.